Pengaruh Relationship Marketing, Kualitas Pelayanan, Dan Penetapan Harga Terhadap Tingkat Kepuasan Konsumen (Studi Kasus Pada Tingkat Kepuasan Konsumen Jasa Pelayanan Grab Bike Di Rembang Kota) - Ahmad Fathur Rizky; Syaiko Rosyidi; Dian Anita Sari (Jurnal Mirai Management, 2023)
Finding evidence that relationship marketing, service quality, and pricing had an effect on consumer satisfaction with Grab bike services in Rembang Kota was the goal of this study. Rembang Kota residents who had used Grab bike services were the subjects of this research. One hundred people were randomly selected to participate in the study's sample. Multivariate linear regression analysis utilising SPSS 24 software for data processing is a common method of conducting statistical analysis. The study's findings show that in Rembang Kota, both service quality and pricing are important in determining how satisfied customers are with Grab bike services. Despite their importance, the relationship marketing, service quality, and pricing variables were only able to influence customer satisfaction by a combined 83.6%, with the remaining 16.4% influenced by factors not included in the analysis. Keywords : Relationship Marketing, Service Quality, Pricing and Customer Satisfaction